Role of Oxidative Stress in the Senescence Pattern of Auditory Cells in Age-Related Hearing Loss - Luz del Mar Rivas-Chacón; Sofía Martínez-Rodríguez; Raquel Madrid-García; Joaquín Yanes-Díaz; Juan Ignacio Riestra-Ayora; Ricardo Sanz-Fernández; Carolina Sánchez-Rodríguez (Antioxidants)
Age-related hearing loss (ARHL) is an increasing and gradual sensorineural hearing dysfunction. Oxidative stress is an essential factor in developing ARHL; additionally, premature senescence of auditory cells induced by oxidative stress can produce hearing loss. Hydrogen peroxide (H2O2) represents a method commonly used to generate cellular senescence in vitro. The objective of the present paper is to study H2O2-induced senescence patterns in three auditory cell lines (House Ear Institute-Organ of Corti 1, HEI-OC1; organ of Corti, OC-k3, and stria vascularis, SV-k1 cells) to elucidate the intrinsic mechanisms responsible for ARHL. The auditory cells were exposed to H2O2 at different concentrations and times. The results obtained show different responses of the hearing cells concerning cell growth, β-galactosidase activity, morphological changes, mitochondrial activation, levels of oxidative stress, and other markers of cell damage (Forkhead box O3a, FoxO3a, and 8-oxoguanine, 8-oxoG). Comparison between the responses of these auditory cells to H2O2 is a helpful method to evaluate the molecular mechanisms responsible for these auditory cells’ senescence. Furthermore, this in vitro model could help develop anti-senescent therapeutic strategies for the treatment of AHRL.